Fenomena Perubahan Strategi Pemasaran dalam Menghadapi Tantangan di Era Digital - Tarisa Aulia Ananda; Nabilla Kusuma Dewi; Mohamad Zein Saleh (Pusat Riset dan Inovasi Nasional, 2023)
Marketing strategy changes need to be made to face challenges in the digital era. The main factor influencing the change in marketing strategy is the change in consumer behaviour. Organisations must change the way they understand consumer preferences and desires because consumers today have greater access to information through the internet and social media. The purpose of this research is to analyse what are the phenomena of marketing strategy changes in facing challenges in the digital era. This research method is a literature study. The result of this study is that marketing strategies must be innovative and creative due to shifts in consumer behaviour, industry issues, and the pace of technological progress. In the digital era, managing change is crucial to overcoming challenges and capitalising on opportunities. In addition, the government encourages business owners to use technology to help their management procedures. Companies can succeed in today's highly competitive digital market by using creative and data-driven marketing methods. Organisations are expected to effectively manage change, adopt new technologies, and take advantage of new possibilities. Future business success depends not only on mastering technology, but also on the ability to innovate, adapt, and have a thorough understanding of market dynamics.